SALL4 in gastrointestinal tract cancers: upstream and downstream regulatory mechanisms - Tairan Wang; Yan Jin; Mengyao Wang; Boya Chen; Jinyu Sun; Jiaying Zhang; Hui Yang; Xinyao Deng; Xingyue Cao; Lidong Wang; Yuanyuan Tang (BMC, 2024)
Abstract Effective therapeutic targets and early diagnosis are major challenges in the treatment of gastrointestinal tract (GIT) cancers. SALL4 is a well-known transcription factor that is involved in organogenesis during embryonic development. Previous studies have revealed that SALL4 regulates cell proliferation, survival, and migration and maintains stem cell function in mature cells. Additionally, SALL4 overexpression is associated with tumorigenesis. Despite its characterization as a biomarker in various cancers, the role of SALL4 in GIT cancers and the underlying mechanisms are unclear. We describe the functions of SALL4 in GIT cancers and discuss its upstream/downstream genes and pathways associated with each cancer. We also consider the possibility of targeting these genes or pathways as potential therapeutic options for GIT cancers.